Identification of a Resistance Gene bls1 to Bacterial Leaf Streak in Wild Rice Oryza rufipogon Griff. - Wen-ai HE; Da-hui HUANG; Rong-bai LI; Yong-fu QIU; Jian-dong SONG; Hai-ning YANG; Jia-xing ZHENG; Yue-yue HUANG; Xiao-qiong LI; Chi LIU; Yue-xiong ZHANG; Zeng-feng MA; et al. (Journal of Integrative Agriculture, 2012)
Bacterial leaf streak (BLS) of rice, caused by Xanthomonas oryzae pv. oryzicola (Xoc) is a worldwide destructive disease. Development of resistant varieties is considered to be one of the most effective and eco-friendly ways to control the disease. However, only a few genes/QTLs having resistance to BLS have been identified in rice until now. In the present study, we have identified and primarily mapped a BLS-resistance gene, bls1, from a rice line DP3, derived from the wild rice species Oryza rufipogon Griff. A BC2F2 (9311/DP3//9311) population was constructed to map BLS-resistance gene in the rice line DP3. The segregation of the resistant and susceptible plants in BC2F2 in 1:3 ratio (χ2=0.009, χ20.05, 1=3.84, P>0.05), suggested that a recessive gene confers BLS resistance in DP3. In bulked segregant analysis (BSA), two SSR markers RM8116 and RM584 were identified to be polymorphic in resistant and susceptible DNA bulks. For further mapping the resistance gene, six polymorphic markers around the target region were applied to analyze the genotypes of the BC2F2 individuals. As a result, the BLS-resistant gene, designated as bls1, was mapped in a 4.0-cM region flanked by RM587 and RM510 on chromosome 6.